Penerapan Model Pembelajaran Problem Based Learning (PBL) Berbantu Media Wizeer.Me untuk Meningkatkan Hasil Belajar IPA - Rizki Tri Noviani; Susilawati Susilawati; Erna Labudasari (CV. ULIL ALBAB CORP, 2024)
This researcher aims to: 1) utilize learning media based on the Problem Based Learning learning model assisted by wizzer.me media in science subjects; 2) find out what factors hinder the improvement of student learning outcomes at SD Negeri III Lohbener; 3) find out to what extent the wizzer.me learning media is able to improve student learning outcomes in science subjects at SD Negeri III Lohbener, Indramayu Regency. This research uses stages: Planning, Action, Observation and Evaluation. This research was carried out at SD Negeri III Lohbener, which is located in Lohbener village, Lohbener sub-district, Indramayu Regency. Data sources were obtained through: interviews, observations, documentation, cycle I activities, cycle II activities. Thus, from the statement above, the researcher can conclude that: 1) through the use of assisted media, namely wizzer.me, in collaboration with Problem Based Learning learning media, it turns out that there are many benefits, including: (a) the existence of assisted media, wizzer.me, students are able to understand the material which has been conveyed, (b) the use of media with the Problem Based Learning learning model in learning is very effective and suitable for improving student learning outcomes (c) students study material continuously according to students' needs without making them feel bored or bored in learning. 2) The obstacle in using wizzer.me assisted media is that when accessing requires internet with full signal strength and with the many features of wizzer.me there are still paid features to be able to access the media. 3) Using the Problem Based Learning learning model assisted by wizzer.me media is able to improve student learning outcomes in science subjects, this is because students are interested in using wizzer.me media and this media is able to strengthen students' memory of the material presented by the teacher.